Vertical Land Motion Due To Present‐Day Ice Loss From Greenland's and Canada's Peripheral Glaciers - D. Berg; V. R. Barletta; J. Hassan; E. Y. H. Lippert; W. Colgan; M. Bevis; R. Steffen; S. A. Khan (Geophysical Research Letters)
Abstract Greenland's bedrock responds to ongoing ice loss with an elastic vertical land motion (VLM) that is measured by Greenland's Global Navigation Satellite System (GNSS) Network (GNET). The measured VLM also contains other contributions, including the long‐term viscoelastic response of the Earth to the deglaciation of the last glacial period. Greenland's ice sheet (GrIS) produces the most significant contribution to the total VLM. The contribution of peripheral glaciers (PGs) from both Greenland (GrPGs) and Arctic Canada (CanPGs) has not carefully been accounted for in previous GNSS analyses. This is a significant concern, since GNET stations are often closer to PGs than to the ice sheet. We find that, PGs produce significant elastic rebound, especially in North and East Greenland. Across these regions, the PGs produce up to 32% of the elastic rebound. For a few stations in the North, the VLM from PGs is larger than that due to the GrIS.